The Influence of Promotion, Service Quality, and Brand Image on Students' Decisions to Study Choose at Universitas Widya Husada Semarang - Pratama, Adri Aditya; Suparmi, Suparmi; Suprapti, Sri (Faculty of Economics and Business UNTAG Semarang, 2023)
The company uses an integrated marketing strategy with the aim of increasing student purchasing decisions in making choices. The purpose of this study was to analyze the effect of promotion, service quality, and brand image on student decisions. This research was conducted using a survey method on 85 students at Universitas Widya Husada Semarang. Data analyzed using multiple linear regression. The results of the study found that promotion, service quality, and brand image had a positive and significant effect on student decisions.